Machining and Tensile Properties of Warm Squeezed 7075 Aluminum Alloy (Journal of University of Babylon for Engineering Sciences, 2023)
This study is aims to improve the properties of aluminum alloy 7075 by conducting heat treatment and mechanical processing. The development experiment was carried out by subjecting the samples to the process of warm squeezing, as well as conventional heat treatment. An improvement in the tensile and machining properties of the samples was noticed after the warm squeezing process. The warm squeezing caused the elongation percentage, yield strength, and the tensile strength of the heat-treated sample to increase by 11%, 40%, and 19% respectively. In addition, a significant increase of 62%, 94% and 191% in the plastic behavior of the squeezed sample was observed during the tensile test at temperatures 200, 250 and 300°C respectively. The mechanical warm squeezing showed an improvement in the machining characteristics of the alloy, as it reduced the surface roughness by 66%, but it increased the cutting force by 34%.